Vitamin D deficiency and visceral adipose tissue in early pregnant women - Rosangela Cisneiros; Juliana Segatto; Eloíse Paixão; Ítalo Bacellar; Marcelo Lima; Álvaro Pacheco; João Guilherme Alves; Francisco Bandeira (BMC, 2021)
Abstract Background We aimed to assess the correlation between vitamin D serum level and visceral fat tissue during early pregnancy. Methods This cross-sectional study was performed in Pernambuco, Brazil. 190 low risk pregnant women (8-16 gestational weeks) were eligible. Visceral adipose tissue was measured by ultrasonography following the technique described by Armellini. The 25(OH) D in serum was determined through chemiluminescence. The Spearman correlation test was applied to evaluate the correlation between vitamin D serum level and VAT, considering p < 0.05 to be significant. Results Vitamin D insufficiency was present in 129 (67.8 %) of subjects. Pregnant women with or without vitamin D deficiency did not differ in age, gestational age, nutritional status and visceral adipose tissue. No correlation between visceral adipose tissue and 25(OH) D was observed: − 0.057 (p = 0.435). Conclusions Maternal visceral adipose tissue and vitamin D serum level are not correlated during pregnancy.